Interneuron migration impairment and brain region-specific DNA damage response following irradiation during early neurogenesis in mice - Lisa Berden; Nicholas Rajan; André Claude Mbouombouo Mfossa; Isabeau De Bie; Emre Etlioglu; Mohammed Abderrafi Benotmane; Mieke Verslegers; Najat Aourz; Ilse Smolders; Jean-Michel Rigo; Bert Brône; Roel Quintens (Cellular and Molecular Life Sciences)
Abstract Embryonic DNA damage resulting from DNA repair deficiencies or exposure to ionizing radiation during early neurogenesis can lead to neurodevelopmental disorders, including microcephaly. This has been linked to an excessive DNA damage response in dorsal neural progenitor cells (NPCs), resulting in p53-dependent apoptosis and premature neuronal differentiation which culminates in depletion of the NPC pool. However, the effect of DNA damage on ventral forebrain NPCs, the origin of interneurons, remains unclear. In this study, we investigated the sequelae of irradiation of mouse fetuses at an early timepoint of forebrain neurogenesis. We focused on the neocortex (NCX) and medial ganglionic eminence (MGE), key regions for developing dorsal and ventral NPCs, respectively. Although both regions showed a typical p53-mediated DNA damage response consisting of cell cycle arrest, DNA repair and apoptosis, NCX cells displayed prolonged cell cycle arrest, while MGE cells exhibited more sustained apoptosis. Moreover, irradiation reduced the migration speed of interneurons in acute living brain slices and MGE explants, the latter indicating a cell-intrinsic component in the defect. RNA sequencing and protein analyses revealed disruptions in actin and microtubule cytoskeletal-related cellular machinery, particularly in MGE cells. Despite massive acute apoptosis and an obvious interneuron migration defect, prenatally irradiated animals did not show increased sensitivity to pentylenetetrazole-induced seizures, nor was there a reduction in cortical interneurons in young adult mice. This suggests a high plasticity of the developing brain to acute insults during early neurogenesis. Overall, our findings indicate that embryonic DNA damage induces region-specific responses, potentially linked to neurodevelopmental disorders.